(untitled) (Revista Internacional de Folkcomunicação, 2021)
Carnival is part of popular culture in Brazil. However, in some regions of the country, this party is not given as much prominence as in others. In the municipality of Santa Cruz do Sul, in Vale do Rio Pardo/RS, the traditional street carnival, with samba schools and blocks, is the subject of disputes between carnival clubs, the government, and the private sector. This article discusses these disputes through the analysis of the two street carnivals that take place in town: the one known as Descida da Júlio, which initially emerges as an act of resistance to changes in the traditional street carnival proposed by the local government; and the one known as Bailinho de Carnaval da Borges, the result of an innovative initiative of local business owners. These two alternatives are analyzed as a means to discuss tensions in the cultural context, through the main national popular festival, having as background matters related to identity and the right to the city. This article follows the theory of cultural studies, in dialogue with the literature on urban and regional development. It is based on literature review and document analysis. The results indicate existing social fissures in the municipality and different society projects. Carnival;. Identity; Popular cultures; Right to the city.